(Dynamic& Static) Forecast of surplus or Deficit of Public budget in Iraq for (2017،2018) - حنتوش ابتسام كاظم (Journal of Economics and Administrative Sciences, 2019)
This research aims at forecasting the public budget of Iraq (surplus or deficit) for 2017 & 2018 through using two methods to forecast. First: forecast budget surplus or deficit by using IMF estimations average oil price per barrel adopted in the public federal budget amounted to USD 44 in 2017 & USD 46 in 2018; Second: forecast budget surplus or deficit by using MOO actual average oil price in global markets amounted to USD 66 in 2018 through applying Dynamic Model & Static Model. Then analyze the models to reach the best one. The research concluded that those estimations of dynamic forecasting model of budget surplus or deficit for 2017 & 2018 gives good reliable results for future periods when using the actual average oil price according to the Iraqi MOO estimates.